Experimental evaluation of the wake characteristics of cross flow turbine arrays. (1st September 2017) - Ordonez-Sanchez, Stephanie; Sutherland, Duncan; Payne, Grégory S.; Bruce, Tom; Gebreslassie, Mulualem; Belmont, Michael R.; Moon, Ian
Abstract: One key factor in the exploitation of tidal energy is the study of interactions of turbines when working in tidal turbine farms. The Momentum Reversal and Lift (MRL) turbine is a novel cross flow turbine. The three blades rotate around a common central horizontal axis which is parallel to their own axis and perpendicular to the flow. The novelty of the MRL turbine is that it relies on the combination of both lift and momentum reversal (drag) for energy extraction. Scaled MRL turbine models of 0.164 m in diameter were used to characterise the flow in three different tidal array settings. Detailed maps of axial velocity profiles and velocity deficits downstream of the turbine are presented, enabling the visualisation of characteristic flow patterns. The results show that the MRL generates lower velocity deficits and turbulence intensities in the near wake than those associated with horizontal axis turbines. The downstream wake was not completely symmetrical which was related to the geometry of the device but also due to the flow developed in the flume. Amongst the three array configurations studied, a fence of turbines with the lowest separation provided the highest power output. Abstract : Highlights: Experimental analysis of the power performance of a novel cross flow turbine. Analysis of the vertical variation of the axial velocity and turbulence intensity of a single cross flow turbine. Detailed maps of axial velocity profiles and velocity deficits downstream of the turbine are presented for the first time for a cross flow single turbine and three different turbine array configurations.